2019
DOI: 10.1002/jhbp.672
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of acute cholecystitis after cardiovascular surgery

Abstract: Background Acute cholecystitis (AC) after cardiovascular surgery (CS) tends to have a serious postoperative course; however, there are few reports of AC after CS. In this study, we investigated the clinical features of AC after CS. Method Of 26 patients who underwent surgery for AC after CS between 2001 and 2018 were investigated. Of these patients, the severity of AC, onset time, surgical outcomes, and postoperative pathological findings were evaluated. Results Grade III accounted for 46% (12/26) of the AC af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Pathological findings revealed gangrene in all patients. Ueno et al 1 also reported that gallbladder drainage for AC after CS was insufficient by itself. Furthermore, Rady et al 24 and Melloul et al 25 also reported that gallbladder drainage cannot be expected to be effective in gangrenous cholecystitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathological findings revealed gangrene in all patients. Ueno et al 1 also reported that gallbladder drainage for AC after CS was insufficient by itself. Furthermore, Rady et al 24 and Melloul et al 25 also reported that gallbladder drainage cannot be expected to be effective in gangrenous cholecystitis.…”
Section: Discussionmentioning
confidence: 99%
“…There are several risk factors for acute cholecystitis (AC), including a history of cardiovascular disease 1 . Some researchers have reported that the incidence rate of AC occurring after cardiovascular surgery (CS) is 0.5%‐6.0% and the mortality rate is 15%‐42% 2–9 .…”
Section: Introductionmentioning
confidence: 99%